PENINGKATAN KETERAMPILAN MEMBACA SISWA MELALUI PENDEKATAN MODEL ARCS DI KELAS IV SD NEGERI 111 PIDOLI DOLOK - Siti Jabeda Siregar; Resdilla Pratiwi; Parulian Siregar (IICLS (Indonesian Institute for Corporate Learning and Studies), 2024)
This research aims to apply the ARCS model to students in class IV of SD Negeri 111 Pidoli Dolok and investigate whether the Indonesian language learning outcomes of these students have improved. This research uses the classroom action research (PTK) method. This study used a cycle design, cycle I and cycle II, with a population of 24 students from class IV. Observation and testing were the research instruments used. This research utilized qualitative descriptions, quantitative descriptions, and validity and reliability tests to analyze the data. The results of this research show that the ARCS model approach shows that students still found several problems in the first cycle, with an average score of 71.88% (fair), and then improved in the second cycle, with an average score of 95% (very good). . Based on students' learning results in the first cycle, they obtained a classical completeness score of 71,88%, and in the second cycle, they obtained a completeness score of 92,86%. Therefore, we can conclude that the implemented ARCS model approach effectively enhances student learning outcomes.